Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2014 Asia-Pacific 2014
DOI: 10.1109/apsipa.2014.7041735
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison for 2 by 2 MIMO system using single leaky coaxial cable over WLAN frequency band

Abstract: In linear service areas such as a tunnel and along railways, leaky coaxial cable (LCX) is widely used as antenna for radio communication. Usually, one LCX is utilized as one antenna. Therefore it requires more than one LCX to configure an multi-input multi-output (MIMO) system. We have recently proposed a method that one single LCX can be utilized as two antennas by feeding different RF transmit signals to each end of the proposed cable. In this paper, we compare 2× 2 MIMO system performance using the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…m is set as -1 to avoid radiated harmonics. It is possible to change the main radiation angle of the LCX cable by adjusting the direction of the slot and the value of P. Figure 2 shows the bidirectional radiation property of the LCX when inputting signals to both side of the cable without the terminating resistor [21]. Two different peak directivities are obtained and the crossing angle is about 2θ −1 degree, their radiation characteristics have low correlation with each other.…”
Section: I L C X S T R U C T U R E a N D R A D I A T I O N P R O mentioning
confidence: 99%
See 1 more Smart Citation
“…m is set as -1 to avoid radiated harmonics. It is possible to change the main radiation angle of the LCX cable by adjusting the direction of the slot and the value of P. Figure 2 shows the bidirectional radiation property of the LCX when inputting signals to both side of the cable without the terminating resistor [21]. Two different peak directivities are obtained and the crossing angle is about 2θ −1 degree, their radiation characteristics have low correlation with each other.…”
Section: I L C X S T R U C T U R E a N D R A D I A T I O N P R O mentioning
confidence: 99%
“…Here, one LCX cable is treated as only one antenna for usage. Researches in [21][22][23][24] show that LCX cable has bi-directional property and one LCX can be utilized as two antennas for 2-by-2 LCX multiple input multiple output (MIMO) system. In addition, a 4-by-4 LCX-MIMO system has been proposed in [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of MIMO channel becomes worse when two cables are closely spaced. Different from a 2-by-2 LCX-MIMO system using two LCXs, the research results in [13]- [16] show that we can utilize one LCX as two antennas for the configuration of the 2-by-2 LCX-MIMO system. The results show that the peak directivity of propagation angles of LCX usually is highly relative to the signal wavelength, LCX slot period and relative permittivity of insulator.…”
Section: Introductionmentioning
confidence: 99%
“…The results in [2] confirm that, over 2.4 GHz frequency band, the proposed MIMO channel using a single LCX cable can realize good 2 Â 2 channel condition even within a highly correlated propagation condition. The 2 Â 2 MIMO performance comparison between that using the LCX cable and using Omni-direction antenna has been reported with simulated results in [3] and with experimental evaluation in [4]. It also showed that by adjusting the period of slot, we can use one composite cable, which consists of a pair of LCX cables with different radiation directivities, to configure a 4 Â 4 MIMO channel.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently proposed a method that one single LCX cable can be used as two antennas [2,3,4,5,6]. When different RF transmit signals are fed to each end of the cable, the single LCX can work as two antennas.…”
Section: Introductionmentioning
confidence: 99%